Peran TikTok dalam Membangun Tren Fashion sebagai Media Dakwah - Badik, Ach. Riyadhul (Journal of Islamic Communication Studies, 2026)
This study examines the role of TikTok in shaping fashion trends among Generation Z university students while also exploring the platform’s potential as a medium for da‘wah. The advancement of digital technology and the dominance of visual culture on TikTok have positioned the platform as a primary space for students to seek outfit inspiration, express self-identity, and construct their everyday style. Employing a qualitative method, the research draws on in-depth interviews with ten Generation Z students who are active TikTok users, complemented by direct observation and a literature review. The findings reveal that students become familiar with fashion trends through repeated exposure on the For You Page (FYP), interactions with content creators, and social indicators such as likes, comments, and content virality. The integration of TikTok Shop further facilitates fashion consumption through fast and seamless transactions, although several students demonstrate selective and cautious purchasing behavior. Another significant finding indicates that fashion trends influence not only aesthetic preferences but also the formation of self-identity, self-confidence, and students’ perceptions of appropriate and moderate appearance. Within the context of da‘wah, ethical values such as modesty, neatness, financial prudence, and self-control appear to be internalized in the ways students select and adapt fashion trends. The study concludes that TikTok holds substantial potential as an effective medium for digital da‘wah through visual, creative, and everyday-oriented approaches that resonate closely with youth culture.